2013
DOI: 10.1371/journal.pone.0058361
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the RANKL/RANK/OPG System Is Associated with Bone Metastasis in Human Non-Small Cell Lung Cancer

Abstract: BackgroundHuman non-small cell lung cancer (NSCLC) patients exhibit a high propensity to develop skeletal metastasis, resulting in excessive osteolytic activity. The RANKL/RANK/OPG system, which plays a pivotal role in bone remodeling by regulating osteoclast formation and activity, is of potential interest in this context.Materials and MethodsReverse transcriptase polymerase chain reaction, western blotting, and immunohistochemical analysis were used to examine the expression of RANKL, RANK, and OPG in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 44 publications
(49 reference statements)
6
54
0
Order By: Relevance
“…Higher RANKL and OPG expression were observed in more advanced metastatic tumours (Po0.05). Higher RANKL expression was found in poorly differentiated tumours (Peng et al, 2013). A summary of these findings is reported in Table 5.…”
Section: Discussionmentioning
confidence: 86%
“…Higher RANKL and OPG expression were observed in more advanced metastatic tumours (Po0.05). Higher RANKL expression was found in poorly differentiated tumours (Peng et al, 2013). A summary of these findings is reported in Table 5.…”
Section: Discussionmentioning
confidence: 86%
“…The prognostic significance of OPG has already been demonstrated in a variety of malignancies, including non-small cell lung cancer (NSCLC), gastric, colorectal, and bladder urothelial cancers [8][9][10][11]. In a recent study of NSCLC, high OPG expression was significantly associated with adverse clinical features, such as advanced tumor stage and lymph node involvement [9].…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple lines of evidence indicating that abnormal expression of the RANKL/RANK/OPG molecular triad mediates tumor progression and metastasis in a wide range of malignancies, including breast, prostate, colorectal, lung, bladder and gastric cancers [6][7][8][9][10][11]. It has been demonstrated that the RANKL/RANK/ OPG system plays a critical role in the crosstalk between cancer cells and the bone microenvironment, promoting a vicious cycle between bone resorption and tumor growth in bone [12].…”
Section: Introductionmentioning
confidence: 99%
“…No associations were observed between serum OPG and risk of cancer and cancer-related mortality in the 13 respiratory system. In human non-small cell lung cancer (NSCLC) tissue samples, significantly stronger immunostaining for OPG, RANKL and RANK were observed in bone metastases than in tumor cells at the primary site (29). Furthermore, the RANKL:OPG ratios were significantly higher in bone metastases compared with primary NSCLC tissue samples (29).…”
Section: Discussionmentioning
confidence: 99%